PENGARUH VARIASI KONSENTRASI BAHAN TAMBAH FLY ASH DAN TERAK BAJA DITINJAU DARI KUAT TEKAN BETON - Fitriadewi, Tina; Priyanto, Kusdiman Joko; Gunarso, Gunarso (Civil Engineering, Faculty of Engineering, Universitas Tunas Pembangunan Surakarta, 2024)
Concrete as the basic material of the structure in the construction of buildings is composed of hardening a certain mixture of water, cement, and aggregate. Concrete material is familiar in the field of Civil Engineering, because almost every building uses concrete as the main structure and complement, be it bridges, water buildings, or buildings. Because concrete is a composite material, the quality of concrete depends on each of the forming materials (Tjokrodimuljo. K,1996). This study used fly ash and steel slag added materials. In this study using an experimental method that aims to determine the effect of adding fly ash and steel slag levels with a percentage of fly ash 10% and steel slag 20%, fly ash 20% and steel slag 10% from the use of cement and fine aggregates and using conventional concrete as a comparison , and the cement water factor is determined to be the same in all variations, which is 0.45. Until thel used is cylindrical (d = 15cm; h = 30cm), the quality of concrete is planned to be 20 MPa. The number of samples is 18 pieces, each variation consists of 6 pieces tol, 3 samples for concrete compressive strength aged 7 days and 3 samples for concrete compressive strength aged 28 days. In the slump test, there was a reduction in the slump value, which was 12 cm for conventional concrete, 11 cm for variation I concrete mixture and 8 cm for variation 2 concrete mixture. The results of the compressive strength test showed an increase in maximum compressive strength at the age of 7 & 28 days with a percentage of fly ash 20% and steel slag 10% which was 19.91 MPa & 29.82 MPa and the lowest compressive strength occurred in conventional concrete, which was 16.32 MPa at the age of 7 days and 25.19 Mpa at the age of 28 days. With a percentage increase of 15.5% from conventional concrete